INTERGENERATIONAL CHANGES IN GENDER EQUALITY AND GENDERED ELECTORAL CHOICES: X, Y, AND Z GENERATIONS IN TÜRKİYE (Proceedings of the World Conference on Women’s Studies, 2026)
Gender is an interdisciplinary topic essential for understanding society and its development. Social expectations, cultural norms, economic conditions, education, technology, and media influence societal gender roles across generations. Gender roles are learned through socialization and reflect the responsibilities assigned by society. The transformation of gender roles is a significant area of sociological and cultural research. Generations inherit the values and experiences of those before them while creating new identities that match current social, economic, and technological contexts. A person's generation can be a key factor in predicting voting choices. Voting decisions are linked to various gender labels and shape gendered electoral patterns from one generation to another. This study analyzes how intergenerational gender roles and gender equality change within society using a quantitative approach from the perspectives of X, Y, and Z generations. The gendered electoral patterns among these generations are examined by connecting intergenerational shifts in gender roles and gender equality in Türkiye. The aim of studying perceptions across X, Y, and Z generations is to identify differences and similarities in the intergenerational gender equality changes and how these relate to gendered voting choices in Türkiye. The survey involves 500 participants selected through simple random sampling from the X, Y, and Z generations. Data will be gathered using the “Perceptions of Gender Scale” and “The Perceptions of Women in Politics Scale.” This study concluded that individuals from X, Y, and Z generations should be empowered in education and knowledge to evolve their gender perspectives and eliminate gendered electoral choices.
Keywords: intergenerational changes; gendered voting choices; gender equality; gender roles